Electric modulation of the Fermi arc spin transport via three-terminal configuration in topological semimetal nanowires - Zhu, Guang-Yu; Ning, Ji-Ai; Wang, Jian-Kun; Liu, Xin-Jie; Yang, Jia-Jie; Lin, Ben-Chuan; Wang, Shuo (Chinese physics B, 2024)
Spin–momentum locking is a key feature of the topological surface state, which plays an important role in spintronics. The electrical detection of current-induced spin polarization protected by the spin–momentum locking in nonmagnetic systems provides a new platform for developing spintronics, while previous studies were mostly based on magnetic materials. In this study, the spin transport measurement of Dirac semimetal Cd 3 As 2 was studied by three-terminal geometry, and a hysteresis loop signal with high resistance and low resistance state was observed. The hysteresis was reversed by reversing the current direction, which illustrates the spin–momentum locking feature of Cd 3 As 2 . Furthermore, we realized the on–off states of the spin signals through electric modulation of the Fermi arc via the three-terminal configuration, which enables the great potential of Cd 3 As 2 in spin field-effect transistors.